Disturbed fluid responsiveness and lactate/pyruvate ratio as predictors for mortality of septic shock patients - Ahmed Abdalla Mohamed; Ahmed Essam (Egyptian Journal of Anaesthesia, 2016)
Objectives: Evaluation of fluid responsiveness of septic shock patients admitted to surgical ICU and the predictability of non-invasive monitoring and estimated lactate/pyruvate (L/P) ratio for survival of these patients. Patients and methods: The study included 58 septic shocked patients admitted and managed at surgical ICU. After non-invasive determination of baseline hemodynamic data and calculation of shock index (SI-0) and Pleth variability index (PVI-0), all patients received intravenous colloid infusion followed 15-min later by non-invasive re-evaluation for SI-15 and PVI-15. Blood samples were obtained for estimation of blood lactate and pyruvate levels at admission (BLL-0 and BPL-0) and 12-h after fluid resuscitation (BLL-12 and BPL-12) and L/P ratio was calculated. All patients were managed according to the Surviving Sepsis Campaign guidelines and followed up for ICU mortality rate (MR). Results: ICU stay MR was 20.7%. Survival showed negative significant correlation with PVI, L/P ratio and BLL, while it showed positive significant correlation with BPL. Receiver Operating Characteristic (ROC) curve analysis defined baseline and persistently low PVI, high BLL and L/P ratio as significant sensitive predictors for MR, while elevated BPL-12 as significant specific predictor for survival. Regression analysis defined persistently elevated L/P ratio as the highly significant specific predictor, while persistently disturbed SI and PVI could predict mortality as screening tests. Odds ratio for mortality at BLL-0 of >2 mmol/L was 0.0321 (95% CI: 0.0037–0.2755), while it was 4.1111 (95% CI: 1.0702–15.792) at BLL-0 >4 mmol/L. Conclusion: After fluid resuscitation and hemodynamic stability, persistently elevated BLL could predict mortality, while elevated BPL could predict survival of septic shock patients. Continuous non-invasive evaluation of fluid responsiveness judged by PVI and SI could provide sensitive screening for survival outcome of shocked patients. Wider scale comparative studies are mandatory for establishment of discriminative PVI and BLL cutoff points for prediction of survival of shocked patients.